Comparison of CTAB Method and Wizard Genomic DNA Purification System Kit from Promega on DNA Isolation of Local Varities of Rice of South Sumatera - Laila Hanum; Yuanita Windusari; Arum Setiawan; Muharni Muharni; Fikri Adriansyah; Amin Ali Mubarok (Science and Technology Indonesia, 2018)
Research in the molecular field requires DNA with a high degree of purity. Local rice varieties of South Sumatra have different leaf texture so that in isolation process to obtain DNA with high purity level required the right method. This study aims to compare the quality and quantity of purity of local rice insulation of local rice varieties of South Sumatra with different methods of CTAB and Wizard Genomic DNA Purification System Kit from Promega. The research was conducted from August 2015 to December 2015 at the Laboratory of Microbiology and Genetics and Biotechnology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Sriwijaya University. The method used is DNA isolation method Wizard Genomic DNA Purification System Kit from promega and CTAB. Based on research that has been done result of DNA visualization showed that DNA isolate CTAB method still have smears while DNA isolate method of Wizard Genomic DNA Purification System Kit from promega not. The average DNA isolate concentration of Wizard Genomic DNA Purification System Kit method is A260 / 280 = 1.853 μg / ml. The average DNA isolate concentration of CTAB method is A260 / 280 = 1,705 μg / ml. Isolation of Rice DNA of local variety of South Sumatera using DNA method of Genomic DNA Purification System Kit from promega has higher quality and quantity compared to CTAB method.